2012
DOI: 10.1371/journal.pone.0041031
|View full text |Cite
|
Sign up to set email alerts
|

Infections with Avian Pathogenic and Fecal Escherichia coli Strains Display Similar Lung Histopathology and Macrophage Apoptosis

Abstract: The purpose of this study was to compare histopathological changes in the lungs of chickens infected with avian pathogenic (APEC) and avian fecal (Afecal) Escherichia coli strains, and to analyze how the interaction of the bacteria with avian macrophages relates to the outcome of the infection. Chickens were infected intratracheally with three APEC strains, MT78, IMT5155, and UEL17, and one non-pathogenic Afecal strain, IMT5104. The pathogenicity of the strains was assessed by isolating bacteria from lungs, ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 30 publications
5
38
0
Order By: Relevance
“…A previous study by Vimont et al (16) confirmed that the inflammatory responses of kidney cells after infection with ST131 versus non-ST131 were comparable. Also, Horn et al (51) observed similar histopathological outcomes in lung tissues after infection with pathogenic versus fecal avian E. coli. These observations, together with our results, suggest that the fitness and epidemiological success of ST131 strains are more relevant in the upstream steps involved at the onset of infection.…”
Section: Discussionmentioning
confidence: 81%
“…A previous study by Vimont et al (16) confirmed that the inflammatory responses of kidney cells after infection with ST131 versus non-ST131 were comparable. Also, Horn et al (51) observed similar histopathological outcomes in lung tissues after infection with pathogenic versus fecal avian E. coli. These observations, together with our results, suggest that the fitness and epidemiological success of ST131 strains are more relevant in the upstream steps involved at the onset of infection.…”
Section: Discussionmentioning
confidence: 81%
“…These pathogens can causes septicemia resulting in death and pericarditis, airsacculitis, and perihepatitis (Horn et al, 2012) of chickens. These pathogens can cause foodborne pathogen contamination for humans (Cruchaga et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Although (Nakazato et al, 2009;Jakobsen et al, 2010). Avian pathogenic E. coli causes yolk-sac infections, respiratory-tract infections, bloodstream infections and colibacillosis (Yang et al, 2004;Horn et al, 2012). Transmission of these diseases accounts for significant losses for poultry producers (Ewers et al, 2009).…”
Section: Introductionmentioning
confidence: 99%